1971
DOI: 10.1017/s0022112071002337
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear wave-number interaction in near-critical two-dimensional flows

Abstract: This paper deals with a system of equations which includes as special cases the equations governing such hydrodynamic stability problems as the Taylor problem, the Bénard problem, and the stability of plane parallel flow. A non-linear analysis is made of disturbances to a basic flow. The basic flow depends on a single co-ordinate η. The disturbances that are considered are represented as a superposition of many functions each of which is periodic in a co-ordinate ξ normal to η and is independent of the third c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…The equation has been derived for many, mainly hydrodynamical, nonlinear stability problems, such as (binary) fluid convection [30], [34], Poiseuille flow [35], chemical reactions [26], and so on. In DiPrima et al [11] and Newell [29] it has been shown that the Ginzburg-Landau equation generically appears as a modulation, or amplitude/envelope, equation for general systems at the onset of pattern formation. Recently, some important steps have been made toward a rigorous proof of its mathematical validity as a modulation equation ([23], [10], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…The equation has been derived for many, mainly hydrodynamical, nonlinear stability problems, such as (binary) fluid convection [30], [34], Poiseuille flow [35], chemical reactions [26], and so on. In DiPrima et al [11] and Newell [29] it has been shown that the Ginzburg-Landau equation generically appears as a modulation, or amplitude/envelope, equation for general systems at the onset of pattern formation. Recently, some important steps have been made toward a rigorous proof of its mathematical validity as a modulation equation ([23], [10], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…for a bifurcation/control parameter A close to a A~ at which a stationary laminar solution becomes linearly unstable) has been developed in refs. [2,15,17]. However (1.1) is only the G(1) part of a more complicated equation.…”
Section: Introductionmentioning
confidence: 99%
“…The equation has been derived by many authors, in various ways. The earliest papers in which the Ginzburg-Landau equation is derived are: Newell and Whitehead [11], Stewartson and Stuart [12], DiPrima, Eckhaus and Segel [13]. In these papers the authors start the analysis by investigating the linear stability of a basic (laminar) solution as a control parameter R is varied.…”
Section: Introductionmentioning
confidence: 99%